Millstones, Stumbling Blocks, and Dog Scraps: Children in the Gospels - Admirand, Peter (Biblical theology bulletin, 2012)
In this article I examine the varied and conflicting instances where children are explicitly mentioned in the Gospels and how the often ambiguous interpretation of the child poses some moral and theological problems today. While this article will seek to flesh out what it means to be a child according to the Gospels, it will also grapple with whether, in fact, childlikeness is a state toward which Christians should even aspire. While the message of humility and serving others are the main themes behind Jesus' radical challenge, the passage is problematic when read today in light of the child abuse scandal and the reality of child soldiers. The simplicity, vulnerability, and helplessness of the child are not the best attributes for most of us—adult or child—to embrace in the context of rampant injustice and abuse.